English for Non English Departments at Brawijaya University: How Essential? - Indah Winarni (TEFLIN, 2005)
Abstract: For years, English has been a compulsary subject for the stuÂdents of non-English departments (henceforth English for SNED). The success of English for SNED at the tertiary level of education has largely been questioned due to various constraints in all levels of its operation. Related to the large resources involved, overall evaluation is necessary. This can be started with analysis of needs, which, in a large organization like university, should be done in two stages (Coleman, 1988). While the present study does not pretend that it could be regarded as Colemans first stage of needs analysis, it would offer a significant contribution to such an undertaking. Carried out in Brawijaya University, this study was aimed at describing, through a set of questionnaires, the perception of graduates, English instructors and subject lecturers on (1) the aim of English for SNED, and (2) the role of references written in English in the level of study programs. As previous studies suggested, conflicting aims of EngÂlish for SNED in the perception of respondents were identified. This study delienated four different groups with regards to the use of references written in English in the level of study programs.